2013
DOI: 10.1371/journal.pone.0068472
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Circadian Activity and Gene Expression Profiles to Predict Chronotoxicity of Drosophila suzukii Response to Insecticides

Abstract: Native to Southeast Asia, Drosophila suzukii (Matsumura) is a recent invader that infests intact ripe and ripening fruit, leading to significant crop losses in the U.S., Canada, and Europe. Since current D. suzukii management strategies rely heavily on insecticide usage and insecticide detoxification gene expression is under circadian regulation in the closely related Drosophila melanogaster, we set out to determine if integrative analysis of daily activity patterns and detoxification gene expression can predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 83 publications
(141 reference statements)
4
64
0
Order By: Relevance
“…2). The increased male capture in the vacuum samples may be because of differences in D. suzukii activity by sex, as male D. suzukii were found to be more active in laboratory activity bioassays (Hamby et al 2013) and research observations in Japan described females as more "passive" (Kanzawa 1939). It is unsurprising that time of year would impact the sex ratio of trap captures, as D. suzukii may overwinter as mated females and males exhibit greater mortality at cold temperatures (Kanzawa 1936(Kanzawa , 1939Dalton et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…2). The increased male capture in the vacuum samples may be because of differences in D. suzukii activity by sex, as male D. suzukii were found to be more active in laboratory activity bioassays (Hamby et al 2013) and research observations in Japan described females as more "passive" (Kanzawa 1939). It is unsurprising that time of year would impact the sex ratio of trap captures, as D. suzukii may overwinter as mated females and males exhibit greater mortality at cold temperatures (Kanzawa 1936(Kanzawa , 1939Dalton et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…30 Wooded perimeters may serve as a refuge for flies during the overwintering period in temperate regions but also daily for flies seeking cooler temperatures and higher relative humidity. 55,56 Just over a quarter of the Florida strawberry field perimeter was woodland or partial-woodland, and we recommend focusing trap placement in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…Hamby et al (2013) found that detoxification gene activity has daily rhythmic patterns in SWD, with the highest activity at Fig. 9 Age-specific oviposition by SWD at 21°C.…”
Section: Chemical Control and Potential For Insecticide Resistance Dementioning
confidence: 99%